Precise Detection of Gene Mutations in Fine-Needle Aspiration Specimens of the Papillary Thyroid Microcarcinoma Using Next-Generation Sequencing - Feng-xia Yu; Min-xia Hu; Han-xue Zhao; Li-juan Niu; Xue-yu Rong; Wei-hua Li; Qiang Zhu; Jian-ming Ying; Ning Lyu (International Journal of Endocrinology)
Purpose. To assess the feasibility of next-generation sequencing (NGS) to detect mutations in BRAF, RAS, TERT promoter, and TP53 genes in ultrasound-guided fine-needle aspiration (FNA) biopsy samples of the papillary thyroid microcarcinoma (PTMC). Methods. A total of 135 FNA samples out of 135 patients with suspected PTMC were submitted for mutation testing using NGS. NGS was successfully performed in 114 specimens, while the remaining 21 samples were excluded due to insufficient amount/poor quality of DNA and sequencing failure. Of those 114 samples, 72 who were confirmed as having PTMC by postoperative histopathology were enrolled in our study, and the other 42 who had a follow-up with ultrasound were excluded. Mutations of genes including BRAF, NRAS, HRAS, KRAS, TERT promoter, and TP53 were evaluated using NGS. The associations of gene mutations and clinicopathological characteristics of PTMC were analyzed. Results. BRAF mutation was observed in 59 (81.94%) of 72 specimens. This mutation detected in BRAF was p.V600E (c.1799T>A) in exon 15 of all 59 specimens. NRAS mutation was identified in 1 (1.39%) specimen classified as Bethesda III and pathologically confirmed as a follicular variant PTMC. There were no mutations found in TERT promoter or TP53. The tumor with a maximum diameter (Dmax) larger than 5 mm was shown to be significantly correlated with the BRAF mutation in a multivariate analysis (OR 5.52, 95% CI 1.51-26.42, P=0.033). But the BRAF mutation was not found to be significantly associated with the gender or age of patients with PTMC (P>0.05). Conclusions. This study demonstrated that gene mutations in FNA specimens of PTMC could be successfully analyzed with a higher sensitivity using NGS compared to conventional methods for mutation detection. BRAF mutation of p.V600E was statistically associated with PTMC with a Dmax larger than 5 mm.